Modified multiwall carbon nanotubes display either phytotoxic or growth promoting and stress protecting activity in Ocimum basilicum L. in a concentration-dependent manner - Gohari, Gholamreza; Safai, Fatemeh; Panahirad, Sima; Akbari, Ali; Rasouli, Farzad; Dadpour, Mohammad Reza; Fotopoulos, Vasileios (My University, 2020)
Carbon-based materials including multiwall carbon nanotubes (MWCNTs) have been recently implicated in a number of reports dealing with their potential use in agriculture, leading to contradictory findings. In this study, MWCNTs were successfully functionalized with carboxylic acid groups (MWCNTs-COOH) in order to increase water dispersion. Hydroponically cultured sweet basil (Ocimum basilicum L.) seedlings were subjected to four concentrations (0, 25, 50 and 100 mg L-1) of MWCNTs-COOH under three salt stress levels (0, 50 and 100 mM NaCl). An array of agronomic, physiological, analytical and biochemical parameters were evaluated in an attempt to examine the potential use of MWCNTs in plants under optimal and abiotic stress conditions. Application of MWCNTs-COOH at optimum concentration (50 mg L-1) could ameliorate the negative effects of salinity stress by increasing chlorophyll and carotenoids content and inducing non-enzymatic (i.e. phenolic content) and enzymatic antioxidant components (i.e. ascorbate peroxidase (APX), catalase (CAT) and guaiacol peroxidase (GP) activity). Furthermore, MWCNTs-COOH treatments under optimal conditions induced plant growth, while a significant increase (P ≤ 0.01) was recorded in essential oil content and compound profile. On the other hand, biochemical and epifluorescence microscopy evidence suggested that high dosage (100 mg L-1) of MWCNTs-COOH leads to toxicity effects in plant tissue. Overall, the positive response of plants to low concentrations of MWCNTs-COOH under control and abiotic stress conditions renders them as potential novel plant growth promoting and stress protecting agents, opening up new perspectives for their use in agriculture.
Keywords: Abiotic stress; Antioxidant enzymes; Carbon nanotubes; Essential oils; Sweet basil